IPhone & iPad dian zi zhuan an zhi zuo : tou guo techBasic kai fa Arduino, gan ce qi yu lan ya ying yong = Building iPhone and iPad electronic projects - Westerfield, Mike (GoTop Information, Inc., 2016)
Detailed summary in vernacular field.